The impact of social networking sites (Facebook - Tik Tok - Instagram) on students' behavior from the point of view of male and female secondary school teachers in the city of Mosul - Alyaa Sobhei Ahmed, (Journal of College of Education, 2023)
The current research aimed at the impact of social networking sites (Facebook - Tik Tok - Instagram) on students' behavior from the point of view of male and female secondary school teachers in the city of Mosul, and to identify the differences in the level of influence of social networking sites on students' behavior according to the gender variable (males - females). And the variable aspect (right-left) The basic research sample consisted of (200) male and female teachers who were chosen randomly from among the male and female secondary school teachers in the city of Mosul. From its stability by using the alpha-Craw-Nbach equation for the search tool, as the value of the stability coefficient for the social media influence tool reached (81). The researcher used the appropriate statistical means for her research, such as the Alpha Cro-Nbach equation, the Pearson correlation coefficient, the t-test for two independent samples, the degree of severity and the weight percentage. The results showed that there was no significant difference in the level of influence of social networking sites (Facebook - Tik Tok - Instagram) on students' behavior according to the gender variable (male - female) .
Keywords: Social networking sites, Student behavior, Educational institutions, Secondary schools